Handbook of technological Advancements and scientific approaches in fluid mechanics - Walker, Gregg (Auris Reference Limited, 2014)
Fluid mechanics is an active field of research with many unsolved or partially solved problems in science and technology. Fluid mechanics can be mathematically complex. Sometimes the problems can best be solved by numerical methods, typically using computers. The book illustrates the application of technology and scientific approaches in fluid mechanics and enables students new to the science to grasp the concepts in the subject